MINAT GENERASI MILLENIAL UNTUK MEMBELI VIRTUAL TOUR - M. Tanggap Sasmita (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
The Covid-19 pandemic has an impact on the world of tourism due to restrictions on travel activities, resulting in the emergence of alternative virtual travel activities. Virtual tour activities are actually not new, but more popular during the covid-19 pandemic. As a new activity for travel industry needs, it’s need to do basic research for the for marketing activities in the future to be monetize by looking at the quality of service, level of satisfaction, and interest of millennial generation to buy this service. By using cross-tabulation method and descriptive analysis techniques the findings of this study that the quality of good service is in line with the level of satisfaction and interest of millennials to buy virtual tour activities in the future with a range of rp.10.000- Rp .50.000 in each activity. More research is needed to find out the right strategy in marketing virtual tour activities